2008
DOI: 10.1007/s11199-008-9499-y
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the Myth of the Monolithic Male Athlete: A Qualitative Study of Men’s Participation in Athletics

Abstract: A qualitative study using field-based methods examined motivations for participation in collegiate team sports, the psychological and emotional rewards of team membership, and the dynamics of relationships with teammates among male athletes. Previous cross-disciplinary research largely reinforces clear and consistent gender differences within communal and agentic domains. In-depth, oral bibliographic interviews with 11 varsity athletes from basketball and soccer teams were conducted at a university in the USA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…These are men who are guided by public figures such as English soccer star David Beckham; these are men who have not been culturally stamped with the homophobia their fathers' were as youths (Anderson, 2009). Indeed, there is a growing body of literature in which young men today are described as rejecting orthodox or hegemonic tenets of masculinity: the homophobia, misogyny, femphobia, emotional stoicism, and aggressive acts of physical violence that are characteristic of it (Anderson & McGuire, 2010;McCormack & Anderson, 2010a, 2010bMcNair, 2002;Stotzer, 2009;Schrack-Walters, O'Donnell, & Wardlow, 2009;Southall, Nagel, Anderson, Polite, & Southall, 2009).…”
Section: Metrosexual and Inclusive Masculinitiesmentioning
confidence: 99%
“…These are men who are guided by public figures such as English soccer star David Beckham; these are men who have not been culturally stamped with the homophobia their fathers' were as youths (Anderson, 2009). Indeed, there is a growing body of literature in which young men today are described as rejecting orthodox or hegemonic tenets of masculinity: the homophobia, misogyny, femphobia, emotional stoicism, and aggressive acts of physical violence that are characteristic of it (Anderson & McGuire, 2010;McCormack & Anderson, 2010a, 2010bMcNair, 2002;Stotzer, 2009;Schrack-Walters, O'Donnell, & Wardlow, 2009;Southall, Nagel, Anderson, Polite, & Southall, 2009).…”
Section: Metrosexual and Inclusive Masculinitiesmentioning
confidence: 99%
“…Sport might afford an especially good possibility, as teammates often need to establish close friendships with one another-indeed, a recent qualitative study (Schrack-Walters et al 2009) of 11 heterosexual male college basketball and soccer players found that one of the key reasons these men participated in sport was for the close, emotional relationships with their teammates-and more of these will likely involve those of varying sexualities. These friendships may create the space for greater conversations on gender, sexuality, and difference, conversations that have considerable potential for increasing tolerance and reducing inequality.…”
Section: Grade In Schoolmentioning
confidence: 99%
“…Attitudes towards, and beliefs about, student-athletes (e.g., Basow & Spinner, 1984;Baucom & Lantz, 2001;Engstrom & Sedlacek, 1991;Grove & Paccagnella, 1995;Harahousou-Kabitsi & Kabitsis, 1995;Michael, Gilroy, & Shaman, 1984;Schneider, 2001), or the perceived differences between student-athletes and non-athlete students (e.g., Atkins, Morse, & Zweigenhaft, 1978;Grove & Paccagnella, 1995;Harris & Hall, 1978;Harris & Ramsey, 1974;Johnson, Hallinan, & Westerfield, 1992); McMartin & Klay, 1983;Pedersen, 1997;Sailes, 1993;Stone, Perry, & Darley, 1997) are often examined in this research, though the most recent article is from 2001. The role of stereotypes in the academic adjustment of student-athletes is also frequently examined, both in terms of the attitudes and beliefs of university personnel (Cockley & Roswal, 1994;Burgess, 2006;Holland, 2009;Knapp, Rasmussen, & Barhart, 2001;Lawrence, 2009;Lawrence, Hendricks, & Ott, 2007;Lawrence & Ott, 2013;Nanney, 2008;Williams & Pennington, 2006;Wulfsberg, 1989) and self-perceptions (Leonard, 1986;Lewis, 1988;Potuto & O'Hanlon, 2007;Simons, Bosworth, Fujita, & Jensen, 2007;Walters, O'Donnell, & Wardlow, 2009).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%